Investigating the effect of butanediol diglycidyl ether on the crosslinking of nanocellulose - Nazanin Motie (Regional Information Center for Science and Technology (RICeST), 2018)
This study was focused on the preparation of an environmentally friendly nanocellulose based hydrogel in the form of pads. Hydrogels are hydrophilic three dimensional network with crosslinks, swells in water but don’t dissolve. In this research nanofibrillated cellulose and Hydroxyethyl cellulose with different ratio (1:1, 2:1, 3:1) were used to make hydrogel. Also, citric acid which has a significant advantage over other crosslinking agents in terms of toxicity and price, has been used in different amounts of 10% and 20% by weight to crosslink. In order to find optimal hydrogel preparation conditions, FTIR analysis, FESEM, time dependent swelling measurement and evaluating the thermal and rheological properties were performed. Samples with a lower ratio of nanocellulose to hydroxyethyl cellulose were found to be inappropriate due to the loss of their apparent integrity in the swelling measurement. According to FTIR results, cross-linking were performed only in samples with the highest ratio of nanocellulose to hydroxyethyl cellulose in different amounts of citric acid. Therefore, the hydrogels' characteristics were mainly influenced by the ratio of nanocellulose to hydroxyethyl cellulose and the amount of citric acid had less effect on these properties. These two successful final samples showed acceptable properties in other evaluated properties and led to the selection of optimal reactive ratios for the preparation of hydrogels for use in various industries, including the pharmaceutical industry.